2013
DOI: 10.1111/joop.12031
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐analysis of the relationships of age and tenure with innovation‐related behaviour

Abstract: One particularly persistent and prevalent negative age stereotype is that older workers are less innovative and more resistant to change. Because older workers are also more likely to have longer organizational tenure, negative age stereotypes contribute to the perception that long‐tenured workers are less innovative and more resistant to change, too. Guided by human capital theory, this study argues that the capacity to contribute to innovation‐related behaviours (IRB) might actually grow with age and tenure,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
209
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(220 citation statements)
references
References 221 publications
(205 reference statements)
8
209
2
1
Order By: Relevance
“…Findings from previous studies supported this work (i.e. Giuri et al, 2007;Liu et al, 2016;Ng & Feldman, 2013;Watson, 2006). …”
Section: Descriptive Statisticssupporting
confidence: 87%
See 2 more Smart Citations
“…Findings from previous studies supported this work (i.e. Giuri et al, 2007;Liu et al, 2016;Ng & Feldman, 2013;Watson, 2006). …”
Section: Descriptive Statisticssupporting
confidence: 87%
“…Giuri et al (2007Giuri et al ( : 1111 found that there is a relationship between education and innovation capacity. Ng and Feldman (2013) and Liu et al (2016) determined that training has impact on innovation capacity. Previous studies also support first hypothesis (H 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with the notion, several researchers have shown that older workers use action-regulation strategies aimed at changing their environment to adapt to age-related changes (e.g., Wahl, Iwarsson, & Oswald, 2011 ). A second stream of research, on proactive work behavior (e.g., Frese, Garst, & Fay, 2007 ;Parker & Collins, 2010 ), provides further evidence for the notion that older workers exercise agency in the workplace (Ng & Feldman, 2013 ;Van Veldhoven & Dorenbosch, 2008 ). Proactive work behaviors are defi ned as self-initiated, future-and change-oriented behaviors (Grant & Ashford, 2008 ;Parker, Bindl, & Strauss, 2010 ) that may be directed toward different targets at a variety of levels (individual/self, co-workers/team, and the organization; see, e.g., Grant & Ashford, 2008 ;Griffi n, Neal, & Parker, 2007 ).…”
Section: Introductionmentioning
confidence: 82%
“…A different large-scale analysis on over 38,000 workers finds no overall relationship between worker age and job performance (McEvoy & Cascio, 1989). Moreover, a metaanalysis of 98 field studies (comprising nearly ten thousand workers) finds no evidence that older worker are less innovative than younger ones (Ng & Feldman, 2013).…”
Section: Changing Employer Mindsetsmentioning
confidence: 98%